1997
DOI: 10.3758/bf03211890
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries and errors in perception of depth from disparity suggest a multicomponent model of disparity processing

Abstract: In three experiments, asymmetries between the processing of crossed and uncrossed disparities were investigated. The target was a luminance-defined circle concentric to a fixation mark, viewed stereoscopically on a computer monitor for 105msec, Fifteen disparities were presented according to the method of constant stimuli. Observers indicated the apparent direction of target depth relative to fixation. All experiments measured both the accuracy and latency of this response. Experiment 1 showed fewer errors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 27 publications
6
32
0
Order By: Relevance
“…Our judgement of depth magnitude and its associated sign may be processed at different stages alone the cortical pathway and may be subject to different limitations. This is very much along the lines of a proposal made by Landers and Cormack 8 , who also reported a large percentage of stereo anomalous observers in the population for determining the sign but not the magnitude of the depth. They suggested that while there may be a continuous representation of disparity within the visual cortex, attentive readout of disparity may be a multicomponent serial process, having the following stages; starting from detection of disparite areas (local correlation), magnitude of disparity (present clinical stereo tests and the stimulus used in this present study), detection on the basis of disparity polarity 1 ) and finally discrimination of depth polarity.…”
Section: Discussionsupporting
confidence: 78%
“…Our judgement of depth magnitude and its associated sign may be processed at different stages alone the cortical pathway and may be subject to different limitations. This is very much along the lines of a proposal made by Landers and Cormack 8 , who also reported a large percentage of stereo anomalous observers in the population for determining the sign but not the magnitude of the depth. They suggested that while there may be a continuous representation of disparity within the visual cortex, attentive readout of disparity may be a multicomponent serial process, having the following stages; starting from detection of disparite areas (local correlation), magnitude of disparity (present clinical stereo tests and the stimulus used in this present study), detection on the basis of disparity polarity 1 ) and finally discrimination of depth polarity.…”
Section: Discussionsupporting
confidence: 78%
“…Manning, et al, 1987) limits, tolerances for polarity reversal , and rates of development (Birch, Gwiazda, & Held, 1982), for various such mechanisms. However, such findings have also been interpreted as consistent with a model that does not posit distinct disparity pooling mechanisms (Landers & Cormack, 1997). Given the limitations for using each of these methods to assess the distinctness of perceptual mechanisms, an additional approach seems warranted.…”
Section: Functional Organizationmentioning
confidence: 93%
“…In the second manipulation, we varied the target's position in depth relative to fixation. The shift of target position in depth does not affect the sensory uncertainty associated with the two retinal images, but we reasoned that it should impact sensory uncertainty due to reduced sensitivity to stimulus properties, such as binocular disparity away from the plane of fixation (Westheimer & Tanzman, 1956;Blakemore, 1970;Schumer & Julesz, 1984;Landers & Cormack, 1997). We further reasoned that if both sensory noise manipulations have similar consequences from a perceptual inference perspective, they should have similar impacts on behavioral performance.…”
mentioning
confidence: 98%